Monthly fuel usage (of the main engines, generator sets and boilers) of ships travelling to Australian Antarctic Stations - BRYSON, ROB (hasPrincipalInvestigator); BRYSON, ROB (processor); Australian Antarctic Data Centre (publisher)
This indicator is no longer maintained, and is considered OBSOLETE. INDICATOR DEFINITION The quantity of fuel used by ships travelling to Australian Antarctic stations and on Marine Science voyages as measured on a monthly basis and reported in the monthly reports from the Voyage Leaders to the Kingston (Head Office) Logistics Section. TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION The amount of fuel used on ships travelling to Antarctica and on Marine Science voyages, for propulsion and power generation, is proportional to environmental impact due to the emissions released. Marine Gas Oil (MGO), is a marine version of normal diesel and is used on the vessels to power the main engines and generator sets, to provide propulsion and general services to the vessels such as power and heating. IFO 40 (RMC 10) is a light grade fuel oil used by some of the vessels by the Antarctic Division. This fuel is used for the main engines, and in some cases the generators. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Southern Ocean. Frequency: Monthly reports Measurement technique: The figures are obtained by sounding the fuel tanks on the ship and/or a reading from the fuel usage meter. RESEARCH ISSUES Depending on the vessels used by the Antarctic division, future collection of this data may be automated. LINKS TO OTHER INDICATORS SOE Indicator 1 - Monthly mean air temperatures at Australian Antarctic stations. SOE Indicator 2 - Highest monthly air temperatures at Australian Antarctic Stations SOE Indicator 3 - Lowest monthly air temperatures at Australian Antarctic Stations SOE Indicator 4 - Monthly mean lower stratospheric temperatures above Australian Antarctic Stations SOE Indicator 7 - Monthly mean of three-hourly wind speeds (m/s) SOE Indicator 48 - Station and ship person days SOE Indicator 57 - Monthly total of fuel used by station incinerators SOE Indicator 58 - Monthly total of fuel used by station vehicles SOE Indicator 59 - Monthly electricity usage SOE Indicator 60 - Total helicopter hours SOE Indicator 61 - Total potable water consumption SOE Indicator 65 - Station footprint for Australian Antarctic stations